2015
DOI: 10.1039/c5cy00124b
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature CO oxidation on CuO/CeO2catalysts: the significant effect of copper precursor and calcination temperature

Abstract: The performance of CuO/CeO2 catalysts for CO oxidation strongly depends on the type of copper precursor and the calcination temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(76 citation statements)
references
References 72 publications
(97 reference statements)
3
72
0
Order By: Relevance
“…Note that the Cu(I) % is just calculated for comparison and does not represent the accurate content of Cu ? on these CuO/CeO 2 catalysts due to the lower CuO loading and the photoresolution of the spectrometer [40].…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…Note that the Cu(I) % is just calculated for comparison and does not represent the accurate content of Cu ? on these CuO/CeO 2 catalysts due to the lower CuO loading and the photoresolution of the spectrometer [40].…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…42,43 As shown in Table 3, the I sat /I main values of all the catalysts are lower than 0.55, further suggesting the presence of low-valence copper species in these CuO-CeO 2 /SBA-15 catalysts. Furthermore, it is apparent that 3-CCS displays smaller I sat /I main value than the other catalysts, indicating that the stronger interaction between copper species and ceria has induced the reduction of more amounts of Cu 2+ (mainly to Cu + ), 4 which is regarded as the better CO adsorption site in CO oxidation.…”
Section: Xps Studymentioning
confidence: 99%
“…Therefore, increasing attention has been given to the non-noble metal catalysts, particularly CuO-CeO 2 system. Numerous studies have found that the CuO-CeO 2 catalysts display high catalytic activity in the oxidation of CO, [2][3][4][5][6][7] which is comparable to or even higher than that on some noble metals like Pt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[54,71] Therefore, it is considered that the most dominant state of cerium in the obtained materials is the + 4 oxidation state. [71,73,74] According to the literature, the binding energy of Cu 2p 3/2 ranges at 943-935 eV, while the lower binding energy indicates the presence of Cu + species. The main peaks at 529.7-528.8 eV (O') are attributed to the lattice oxygen of the CeO 2 and CuO phase.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%